Headaches, Fevers, and Psalms: Notes on a Coptic Amulet from Oxyrhynchus - Zellmann-Rohrer, Michael (Journal of Coptic studies, 2024)
This article proposes a contribution to the understanding of a fever amulet on paper from medieval Bahnasa (ancient Oxyrhynchus). Its secure Oxyrhynchite provenance makes it rare among magical texts in Coptic, and it is unusually late for manuscripts from that area tout court. Alongside some new readings, the identification of a citation of the Psalms (130[131]) allows the amulet to be situated in the history of the magical use of the Psalter in Egypt. A so far unique Coptic formulary dedicated to the same practice (now in the collection of Duke University) is given a preliminary edition. An appendix also presents a new text and translation of the Oxyrhynchite amulet based on autopsy.